2022
DOI: 10.21203/rs.3.rs-1756422/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relative burden of diarrheal cases in under-five children before and during COVID-19 pandemic in Ethiopia: a retrospective study

Abstract: Background: The burden of diarrhea in under-five children is a problem in Ethiopia. The different measures taken to prevent COVID-19 pandemic are believed to have impact on the burden of diarrhea. However, there is no data that shows the association of COVID-19 pandemic and burden of diarrhea in under-five children. The aim of this study was to assess burden of diarrheal cases and associated factors among under-five children that attended primary health centers before and during COVID-19 pandemic in Addis Aba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A study in Ethiopia reported that there was a decrease of diarrhea during the pandemic although it was found not to be significant. 23 …”
Section: Discussionmentioning
confidence: 99%
“…A study in Ethiopia reported that there was a decrease of diarrhea during the pandemic although it was found not to be significant. 23 …”
Section: Discussionmentioning
confidence: 99%